Mastery of Hanyu Pinyin of Non-native Speakers - Amran, Nur Farrah Atiqah; Yeoh, Yin Yin; Chew, Fong Peng (2022)
Proficiency in third language is a much-needed added value present day. Third language learning has been highlighted in the Malaysia Education Blueprint 2013 - 2025. One of the skills that needs to be mastered by students is communication in social situations using Malay, English and an additional language. There is an increase of trend in primary and tertiary educational institutions in Malaysia offering foreign language courses. Mandarin has become one of the most popular elective course options among students due to the factor of better career opportunities in the future. Hence, the purpose of this study is to examine the non-native speakers’ mastery in Hanyu Pinyin at the early stage. This study uses a survey to answer the main research questions. With the aim of achieving the research main goal, a survey will be conducted accordingly. Questionnaire instruments will be given to the students taking Mandarin language subjects at a public university. The findings of this study are expected to elevate the university, especially the for the academicians to produce high quality graduates with the ability to speak a third language fluently. On top of that, it will also enhance the university's reputation with outstanding student achievement, thus benefiting national development especially in international relations.